2020
DOI: 10.13057/biodiv/d210340
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of microalgae in coastal areas of East Java, Indonesia

Abstract: Abstract. Zakiyah U, Mulyanto, Suwanti LT, Koerniawan MD, Suyono EA, Budiman A, Siregar UJ. 2020. Diversity and distribution of microalgae in coastal areas of East Java, Indonesia. Biodiversitas 21: 1149-1159. Indonesia is well known as one of hotspot for biodiversity, including marine resources. However, Indonesia biodiversity has declined rapidly due to the changes in the aquatic environmental quality as the consequence of human activities. Biodiversity loss has been well studied in larger organisms, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Microalgae are eukaryotic photosynthetic microorganisms found in almost all habitats, both normal and extreme waters such as fresh water, lakes, rivers, oceans, estuaries, brackish, thermophilic, saline, and hyper-saline environments (Leliaert et al, 2012;Selvarajan et al, 2015), including in Indonesian marine waters. Indonesian researchers have found and succeeded in culturing the Glagah and East Java Mixed Microalgae (Suyono et al, 2016(Suyono et al, , 2018Zakiyah et al, 2020). The mixed microalgae then were called consortium (Glagah consortium and East Java consortium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae are eukaryotic photosynthetic microorganisms found in almost all habitats, both normal and extreme waters such as fresh water, lakes, rivers, oceans, estuaries, brackish, thermophilic, saline, and hyper-saline environments (Leliaert et al, 2012;Selvarajan et al, 2015), including in Indonesian marine waters. Indonesian researchers have found and succeeded in culturing the Glagah and East Java Mixed Microalgae (Suyono et al, 2016(Suyono et al, , 2018Zakiyah et al, 2020). The mixed microalgae then were called consortium (Glagah consortium and East Java consortium).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the bacteria are Corynebacterium ulcerans, Corynebacterium bovis, Bacillus cereus, Bacillus megaterium, Pediococcus parvulus, and Staphylococcus vitulinus (Suyono et al, 2018). Zakiyah et al (2020) found microalgae from several beaches in East Java, namely microalgae divisions of Bacillariophyta, Chlorophyta, Cyanophyta, Dinoflagellates, Granuloreticulosa, and Ochrophyta. Study of mixed microalgae from East Java have only limited diversity based on identification at the genus level and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, Indonesia is one of the archipelagic countries with a water area of up to 2/3 of the land, where this water area is the habitat of marine diversity (Zakiyah et al, 2020), one of which consists of macroalgae (Risjani et al, 2020) and microalgae, including diatoms with high diversity (Risjani et al, 2021). Diatoms are a group of microscopic algae that can live in various habitats and abound in various ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…As cosmopolitan organism, microalgae can live in freshwater, brackish water, and marine water. They usually live on the water surface, water columns, and the bottom of the waters and various substrates, ranging from hard to smooth substrates, artificial substrates, and mangroves (Zakiyah et al 2020;Arsad et al 2022). Some microalgae are sedentary by attaching to the rocks and either sensitive or tolerance to water pollution (Tang 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on microalgae have been conducted in various marine areas in Indonesia. In East Java, several studies on microalgae have been carried out in Sempu Island and Siwil Beach Pacitan (Arsad et al 2022), Probolinggo and Situbondo (unpublished data), Trenggalek and Sendangbiru (south coast), Banyuwangi and Situbondo (north coast of East Java), and Pasongsongan and Pamekasan Madura (north and south coast) (Zakiyah et al 2020). In addition, Nafisyah et al (2018) carried out research in mangrove sediments in Probolinggo and found Cryptic occurrence of Chattonella marina var.…”
Section: Introductionmentioning
confidence: 99%